2004
DOI: 10.1126/science.1094982
|View full text |Cite
|
Sign up to set email alerts
|

Direct Spinning of Carbon Nanotube Fibers from Chemical Vapor Deposition Synthesis

Abstract: Many routes have been developed for the synthesis of carbon nanotubes, but their assembly into continuous fibers has been achieved only through postprocessing methods. We spun fibers and ribbons of carbon nanotubes directly from the chemical vapor deposition (CVD) synthesis zone of a furnace using a liquid source of carbon and an iron nanocatalyst. This process was realized through the appropriate choice of reactants, control of the reaction conditions, and continuous withdrawal of the product with a rotating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
921
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,370 publications
(932 citation statements)
references
References 19 publications
7
921
0
4
Order By: Relevance
“…The production of continuous yarns of pure CNTs has been accomplished by "dry-spinning", the mechanical process of spinning either the single-walled CNTs directly from a CVD (chemical vapor deposition) gaseous reaction zone [1,2] or with the multi-walled CNTs previously grown as a vertically oriented CNT forest [3,4] . In contrast, "wet-spinning", the spinning of a "super-acid (100 + %sulfuric acid) suspension" [5] of the single-walled CNTs, produced purely CNT-based continuous fibers.…”
Section: Fugetsu)mentioning
confidence: 99%
“…The production of continuous yarns of pure CNTs has been accomplished by "dry-spinning", the mechanical process of spinning either the single-walled CNTs directly from a CVD (chemical vapor deposition) gaseous reaction zone [1,2] or with the multi-walled CNTs previously grown as a vertically oriented CNT forest [3,4] . In contrast, "wet-spinning", the spinning of a "super-acid (100 + %sulfuric acid) suspension" [5] of the single-walled CNTs, produced purely CNT-based continuous fibers.…”
Section: Fugetsu)mentioning
confidence: 99%
“…For example, prior to 2007, the reported tensile strengths of continuous CNT fibers without a coagulant lay in the range from 0.4 to 1.2 GPa, no matter if they were spun from a suspension. [5][6][7][8][9][10][11][12] Recently, Windle et al reported the synthesis of continuous high-performance CNT fibers with the highest strength value of 9 GPa. [12] This encouraging breakthrough enlightens the use of macroscale CNTs fibers as a structural reinforcement for many applications.…”
mentioning
confidence: 99%
“…Figure 1 shows a typical twisting process. Compared with the existing spinning methods developed by other groups, [5][6][7][8][9][10][11] our twisting method may not be suitable for continuous production of CNT fibers, but the control of the diameters and twisting degrees is more convenient. So the fabricated fibers are ideal systems for the study of CNT macroarchitectures.…”
mentioning
confidence: 99%
“…Among these additives studied CNT may have the potential to improve the mechanical and thermal properties of MgB 2 wires since CNTs have been used as component for a number of composites to improve their mechanical properties. [17,18] Fosshein et al report an enhanced flux pinning in Bi 2 Sr 2 CaCu 2 O 8+x superconductors with embedded CNTs. [19] Yang et al found a significant enhancement in J c (H) for high temperature superconductor by introducing nanorods as columnar pinning centers in to the composites.…”
mentioning
confidence: 99%